Hubungan Kecanduan Game Online Dengan Smartphone di Masa Pandemi Terhadap Keluhan Neck Pain Pada Mahasiswa Fakultas Ilmu Kesehatan UPN Veteran Jakarta Tahun 2021 - Zhafira Salsadhika Banyudewa, (2021)
The COVID-19 pandemic made people do activities at home, to fill students' free time in addition to learning is to play online games. When one really can't escape from playing online games, it is said to be an addiction to online gaming. Neck pain can be felt at the top of the spine feeling pain precisely in the cervical area. The purpose of this study was to analyze the relationship between frequency intensity, duration, and addiction of online games with smartphones to neck pain complaints in students of the Faculty of Health Sciences UPN Veteran Jakarta. The research uses quantitative methods and cross sectional research design. Sample technique with purposive sampling, which obtained samples from 319 students. Results from the Chi Square test obtained that the absence of a relationship of frequency and duration of playing online games with smartphones until complaints of neck pain obtained p-value is 1,000 (p-value > 0.05). Meanwhile, there is a link between online gaming addiction and neck pain complaints obtained p-value 0.003 (p-value < 0.05). Therefore, for students of the Faculty of Health Sciences UPN Veteran Jakarta is more self-controlled in playing online games so as not to overdo it, and maintain health in the neck so as not to cause higher pain.